Intensitas bermain game online mobile playerunknown’s battleground (PUBG) dengan kecenderungan agresivitas pada dewasa awal - Teofanda Reza (Fakultas Psikologi, 2020)
Mobile online gaming is now the trend is mobile battleground playerunknown’s game (PUBGM). In that type of game Battle Royale game, players are required to compete to survive and kill other players. This gives rise to controversy one of which is related as a result of aggressiveness. This research aims to know the relationship between the intensity of playing online games with aggressiveness. The study uses a quantitative research approach with correlational research design. The subject in this study amounted to 201 participants taken using the Purposive sampling technique by assigning special characteristics that fit the research objectives. The instruments used are the Likert scale Brief Aggression Questionnaire (BAQ) and the intensity scale. The result from this study was analyzed using SPSS 25 with product moment Pearson correlation technique where the coefficient of determination (R2) amounted to 0.16 and the correlation coefficient (r) 0.40 amounting to significance value of 0.000 < 0.05. It can be said there is a positive and significant relationship with moderate levels between intensity and aggressiveness. Thus the more a person has a high intensity then the greater the tendency of aggressiveness on them.